OCRL1 Deficiency Affects the Intracellular Traffic of ApoER2 and Impairs Reelin-Induced Responses - Luz M. Fuentealba; Héctor Pizarro; María-Paz Marzolo (Biomolecules, 2024)
Lowe Syndrome (LS) is a rare X-linked disorder characterized by renal dysfunction, cataracts, and several central nervous system (CNS) anomalies. The mechanisms underlying the neurological dysfunction in LS remain unclear, albeit they share some phenotypic characteristics similar to the deficiency or dysfunction of the Reelin signaling, a relevant pathway with roles in CNS development and neuronal functions. In this study, we investigated the role of OCRL1, an inositol polyphosphate 5-phosphatase encoded by the OCRL gene, mutated in LS, focusing on its impact on endosomal trafficking and receptor recycling in human neuronal cells. Specifically, we tested the effects of OCRL1 deficiency in the trafficking and signaling of ApoER2/LRP8, a receptor for the ligand Reelin. We found that loss of OCRL1 impairs ApoER2 intracellular trafficking, leading to reduced receptor expression and decreased levels at the plasma membrane. Additionally, human neurons deficient in OCRL1 showed impairments in ApoER2/Reelin-induced responses. Our findings highlight the critical role of OCRL1 in regulating ApoER2 endosomal recycling and its impact on the ApoER2/Reelin signaling pathway, providing insights into potential mechanisms underlying the neurological manifestations of LS.